(untitled) (Journal of Madenat Alelem, 2012)
Compton profile of transition metal (β-Mn) was calculated employing the renormalized-free-atom (RFA) and free electron models, choosing 3d6-x-4s1-x configuration, whereas (x=0 to 1 step 0.1). This result was compared with experiment values. It is seen that the RFA calculation in 3d64s1 gives a better agreement with the experiment. This theoretical Compton profile data have been used to compute the cohesive energy of Manganese for the first time and compared it with available data.